Analysis of support structures in paralympic nordic skiing in international comparison - an explorative study - Rombach, R.; Wassong, S. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In the Paralympic summer games in London 2012 a before unknown interest in visitors and as well in media presence was obvious. Especially in the track and field disciplines a Paralympic athlete can pursue his athletic career as a full time job. Therefore professionalism in Paralympic sport will continue to gain ground. In Nordic winter sport similar tendencies can be observed if an athlete is successful in Paralympics. A prerequisite however to combine an athletic and professional career are the funding and support system of the different national associations. Various aspects of competitive sport promotion therefore it is important in continuing the success in the field of Nordic winter sport on competitive level.